Responsiveness of Outpatient Care from Patient Perspectives: An Analysis of Administrative Governance and Physical Infrastructure - Fitri, A. Ulfiana; Halima, Nurul; Hardianti, Andi (CV. Social Politic Genius (SIGn), 2025)
The responsiveness of non-medical services is a crucial indicator in determining the governance quality of referral healthcare facilities. The phenomenon of disparities in administrative service performance and the limitations of supporting infrastructure remain operational constraints affecting public satisfaction levels. This study aims to explore and analyze outpatient care responsiveness based on the direct experiences of patients at the Regional General Hospital of Syekh Yusuf, Indonesia. This qualitative study with a descriptive case study design employed a purposive sampling technique involving ten informants, primarily comprising patients as the main data source. Primary data were collected through in-depth interviews, which were validated through source triangulation and non-participant field observations. The thematic analysis revealed five fundamental weaknesses in the service system. First, patients experienced inefficiencies in waiting times due to network information system constraints and bureaucratic complexities in the insurance system. Second, there was a discrepancy in interpersonal communication standards, characterized by fluctuating attitudes and the unfriendliness of the registration counter staff. Third, although the verbal delivery of procedural information was considered adequate, the availability of visual guidance facilities was very limited. Fourth, the cramped and narrow waiting room layout significantly degraded physical comfort standards. Fifth, patients’ smooth physical mobility was compromised by broken escalators and by overlapping elevator use. These empirical findings conclude that the failure to meet service responsiveness expectations stems from institutional managerial oversight deficiencies, rather than medical clinical capabilities. Therefore, management is recommended to immediately upgrade the information system’s operational capacity, establish standard operating procedures for frontline staff etiquette, redesign waiting room capacities, and prioritize maintenance of building accessibility infrastructure for vulnerable patient groups.